(3OjhGf TYQ Uaj GdOjf GdMdis - (3YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe GdSfHSj GdWGFj GdMdj , Uaj GdOjf,J (B750 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde GdEfSGf GdHjGf hef Hg Ydjg aEfi cfJ bHd Cf CTH Ydi GdWhb hCYde eG OhGYi GdThb dgLkG HGdTYQ fXekG hMaXkG GdHGH GdChd ai GdaNQ hGdMeGSI hGdJMQjV Ydi GdQjGSI s
(3BNQgG (B:s
(3deG QaYJ fGQce ddSGQi CfSJ Ydi GdfGQ gOGi GdCSQGQ ePLFJce CQhe efgG bHSkG fhOjJ HCf HhQc ef ai GdfGQ Je GdOjhGf hced HYhf Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B141s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdCOHs